Health Education About Hepatitis Disease for Students at Boarding School: A Quasi-Experimental Study at Sabilul Wafaa Islamic Boarding School - Metilda, Metilda; Manumara, Theophylia Melisa; Oktaviane, Nayla 'Afifah; Ulfah, Nadia Zakia; Ajiziah, Putri Rohmah; Rhomadoni, Reinald Qobly (TRI DHARMA MANDIRI: Dissemination and Downstreaming of Research to the Community (Journal of Community Engagement), 2025)
Based on reports from the Ministry of Health of the Republic of Indonesia, hepatitis-related mortality remains high, with hepatitis B accounting for 51,000 deaths and hepatitis C for 5,942 deaths. Hepatitis is an inflammatory disease of the liver that, if not treated promptly, can progress to serious complications such as liver cirrhosis and hepatocellular carcinoma. This community service activity was conducted among students at Sabilul Wafaa Islamic Boarding School as a preventive effort to reduce the spread of hepatitis. The activity aimed to improve students’ knowledge of hepatitis. A quasi-experimental Design was employed, involving a total of 26 participants. Knowledge levels were measured using a pretest and posttest questionnaire consisting of 10 items, and data were analyzed using a paired t-test to determine differences in mean scores. Following the educational intervention, a significant improvement in knowledge was observed, as evidenced by a posttest score increase from 4.69 ± 0.84 to 8.42 ± 1.14 (p < 0.001). Overall, the activity was effective in increasing students’ knowledge of hepatitis. This program is expected to encourage the dissemination of preventive information, the adoption of clean and healthy living behaviors, and the integration of continuous hepatitis education to assess knowledge retention and the consistency of participants’ preventive behaviors.